Aplicação de nanopartículas em filmes utilizados em embalagens para alimentos - Aouada, Márcia Regina de Moura (2009)
Dispersions composed of chitosan (CS) were obtained by the template polymerization (CS-PMAA) and ionotropic gelatinization (CS-TPP). The nanoparticles were analyzed by FT-IR analysis, particle size, zeta potential, electron microscopy (transmission and scanning), and TGA analysis. The nanoparticles obtained presented a very homogeneous morphology showing a quite uniform particles size distribution and a rather spherical shape. The particle size and zeta potential were dependent on the chitosan concentration used during the preparation method and pH. Different particles were incorporated in the hydroxypropyl methylcellulose (HPMC) films in order to improve their properties. For this, a 3% HPMC (in w:v %) solution was prepared and added in this nanoparticles solutions of both syntheses. The films were characterized by mechanical (tensile, elongation and elastic modulus), barrier [water vapor (WVP) and oxygen], thickness, morphological, and thermal properties. The WVP of the control HPMC film was 0.79 g mm/kPa h m2. The WVP decreased significantly when CS-PMAA nanoparticles were incorporated to HPMC films. For example, WVP decreased to 0.64; 0.59 and 0.47 g mm/kPa h m2 for films containing 59, 82 and 110 nm, respectively. For CS-TPP nanoparticles the WVP decreased to 0.58; 0.45 and 0.33 g mm/kPa h m2 for films containing nanoparticles with 220, 110 and 85 nm, respectively. The same way, the mechanical properties of the HPMC films were strongly improved when CS nanoparticles were incorporated. In this way, HPMC films containing nanoparticles could be considered as promising materials for application in packaging for preservation of foods.